PENERAPAN PENDEKATAN CONTEXTUAL TEACHING AND LEARNING (CTL) UNTUK MENINGKATKAN HASIL BELAJAR IPS SISWA KELAS IV SD NEGERI 148 PEKANBARU - Betty Kristina; Hendri Marhadi; Mahmud Alpusari (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2015)
Abstract: This study was based by the low learning outcomes IPS Elementary School fourth grade students 148 Pekanbaru, with the average grade 61.09. While the value of minimum criteria for completeness (KKM) IPS is 70. Among students who totaled 32 people only 10 people who reached KKM with classical completeness 31, 25%. This study is a Classroom Action Research (CAR) conducted aims to improve learning outcomes IPS Elementary School fourth grade students 148 Pekanbaru. The research problems are: Does the application approach Contextual Teaching and Learning (CTL) can improve learning outcomes IPS Elementary School fourth grade students 148 Pekanbaru. The research was conducted on April 30, 2013 to May 17, 2013. The subjects were fourth grade students of SD Negeri 148 Pekanbaru totaling 32 students. The research was conducted on April 30, 2013 to May 17, 2013. The subjects were Elementary School fourth grade students 148 Pekanbaru totaling 32 students. Data collection instrument was a teacher and student activity sheets and learning outcomes. This research study presents the results obtained from the value of daily tests before action by the average 61.09. In the first cycle to 65.78 by the number of students who completed as many as 13 people. In the second cycle increased to 73.60 by the number of students who completed as many as 26 people. In the third cycle increase value - average students into 82.66 by the number of students who achieve mastery as many as 29 people from 32 the number of students. This proves that the application of the approach of CTL (Contextual Teaching and Learning) can improve learning outcomes IPS Elementary School fourth grade students 148 Pekanbaru.Keywords: Contextual Teaching and Learning (CTL), Social Science Education, Social Science Learning Outcomes